Guided Intra-articular Corticosteroid Injections in the Midfoot. (August 2018) - Protheroe, Derek; Gadgil, Anirudh
Background: Intra-articular corticosteroid injections are used for both their therapeutic and diagnostic function. There is a paucity of literature investigating the efficacy of intra-articular corticosteroid injections into the midfoot. The aim of the study was to identify the efficacy of image guided intra-articular corticosteroid (Methylprednisolone) injections for midfoot osteoarthritis The null hypothesis of this study was there would be no benefit or increase of the Self-reported Foot and Ankle Score (SEFAS) from an intra-articular corticosteroid injection. Methods: SEFAS was collected at 4 and 12 months postinjection. A total of 37 consecutive patients who had 67 midfoot injections were recruited into the study over a 6-month period. Results: The mean SEFAS score preinjection was 17.0, at 4 months postinjection was 31.8 ( P < .001), and 12 months postinjection 21.3 ( P < .14). There was a statistically significant improvement in postinjection SEFAS ( P < .001) at 4 months. The null hypothesis of this study was rejected. Response to the injection was varied but patients with BMI less than 30 had a sustained ( P < .04) symptomatic improvement at 12 months when compared to the obese patients. Conclusion: Our findings support the use of corticosteroid injections as a viable diagnostic and therapeutic option following failed conservative treatment options prior to operative intervention. The results at 4 months were statistically significant with an additional finding of a difference observed between obese and nonobese patients. This may have implications for further educating the patient in effective weight loss that may improve symptom relief from intra-articular injection. Level of Clinical Evidence: Level III, comparative study.